Submission Instructions - Rodrigues Junior, Otavio Luiz (Revista de Direito Civil Contemporâneo, 2018)
The Journal of Contemporary Private Law, ISSN 2358-1433, published quarterly by Editora Revista dos Tribunais, in Brazil, invites academics and researchers to submit unpublished papers for its first issue of 2015, in the following areas: a) jurisprudence related to private law; b) history of private law; c) roman law; d) comparative private law; e) the law of obligations; f) contracts; g) torts; h) property law; i) family law; j) Probate and Succession Law. The mission of RDCC, as provided in the document of its Editorial Content, is the development of Contemporary Private Law based on internationalization, with respect to the theoretical foundations of Private Law and in the search for the contemporary society problem solving. The Journal of Contemporary Private Law will be available both in print and online: [www.revistadostribunais.com.br].